Diaporamas: um estudo crítico de audiovisuais na arte brasileira (1972-1975) - Carvalho, Rosane Andrade de (2021)
This investigation the Brazilian audiovisual production of the 1970s, specifically the sli deshows, slides synchronized to children recorded on cassette or roll, from the analysis of the following works: Curriculum Vitae I and Curriculum Vitae II, by Frederico Morais (1936); Ma tadouro, by Beatriz Dantas (1949) and Paulo Lemos; Eu armário de mim, by Letícia Parente (1930-1991); Natureza (Besame Mucho), by Luiz Alphonsus (1948), and Bichomorto, by Paulo Fogaça (1936-2019). The research objectives are to investigate how this production was con figured in Brazil in the 1970s, how these works are related to the set of artistic proposals that use new technologies in the context of the period as a means of expression, and also to iden tify the strategies adopted by the artists under investigation. For that, newspapers, magazi nes, catalogs, folders, participate and consulted in public and private collections, and classify with the artists that are part of the analysis corpus, personal sources of this research. Through a dialogue between the History of Art and the Visual Culture Studies, I try to unders tand the Works inside the culture and artistic production of the time